Blockade of Interferon‐γ Normalizes Interferon‐Regulated Gene Expression and Serum CXCL10 Levels in Patients With Systemic Lupus Erythematosus. Issue 10 (23rd September 2015) - Welcher, Andrew A.; Boedigheimer, Michael; Kivitz, Alan J.; Amoura, Zahir; Buyon, Jill; Rudinskaya, Alla; Latinis, Kevin; Chiu, Kit; Oliner, Kelly S.; Damore, Michael A.; Arnold, Gregory E.; Sohn, Winnie; et al.
Abstract : Objective: To assess the safety and immunologic impact of inhibiting interferon‐γ (IFNγ) with AMG 811, a human IgG1 monoclonal antibody against IFNγ, in patients with systemic lupus erythematosus (SLE). Methods: Twenty‐six patients with mild‐to‐moderate, stable SLE were administered placebo or a single dose of AMG 811, ranging from 2 mg to 180 mg subcutaneously or 60 mg intravenously. Results: Similar to results previously reported following inhibition of type I IFNs, treatment of SLE patients with AMG 811 led to a dose‐dependent modulation of the expression of genes associated with IFN signaling, as assessed by microarray analysis of the whole blood. The list of impacted genes overlapped with that identified by stimulating human whole blood with IFNγ and with those gene sets reported in the literature to be differentially expressed in SLE patients. Serum levels of IFNγ‐induced chemokines, including IFNγ‐inducible protein 10 (IP‐10), were found to be elevated at baseline in SLE patients as compared to healthy volunteers. In contrast to previously reported results from studies using type I IFN–blocking agents, treatment with AMG 811 led to dose‐related reductions in the serum levels of CXCL10 (IP‐10). Conclusion: The scope and nature of the biomarkers impacted by AMG 811 support targeting of IFNγ as a therapeutic strategy for SLE.